Productive and economic potential of the application of biofertilizer in hybrid corn DAS 3383 - Vera, José; Barzallo, Diego; Villamar, Mónica; Ortiz, Jhonny; Moyano, Gavin; Yugsan, Junina (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The excessive and inappropriate use of synthetic fertilizers has the potential to cause significant environmental and economic issues. The utilization of biofertilizers represents a sustainable and environmentally friendly alternative for the enhancement of crop productivity. Accordingly, the present study evaluated the productive and economic behavior of applying biofertilizers on hybrid corn DAS 3383 under a completely random block design, with five treatments and three repetitions. The following treatments were employed: a control treatment devoid of any fertilization (CONTROL), a conventional treatment comprising NPK fertilization (NPK), a treatment incorporating 5 % biofertilizer (5BIO), a treatment incorporating 15 % biofertilizer (15BIO), and a treatment incorporating 25 % biofertilizer (25BIO). At the 90-day mark, the NPK treatment exhibited the greatest plant height (272.81 cm), while at the 108-day interval, the cob insertion height (170.40 cm) was also the highest. However, the 25BIO treatment yielded the most optimal results in terms of cob length (14.29 cm), diameter (6.07 cm), 1,000-grain weight (31.70 g), and yield (9 t.ha-1). This treatment also demonstrated the highest net benefit ($2,019.10) and favorable profitability (72 %) compared to the other treatments. The results of the orthogonal contrast analysis indicate that there are significant linear effects for the majority of variables, with no discernible quadratic effects. This evidence substantiates the potential of biofertilizers in enhancing maize crop productivity. By repurposing organic waste from the agricultural sector and employing it as an alternative to chemical fertilizers, these findings contribute to the advancement of more sustainable and profitable agricultural practices.